SARS-CoV-2 encoded ORF3a interacts with YY1 to promote latent HCMV reactivation. - Sisi Xia; Xiaoping Huo; Nanfang Liu; Xinyu Liu; Tianyou Wang; Muyi Guo; Chi Zeng; Pin Wan; Jun Chen (PLoS Pathogens)
Human Cytomegalovirus (HCMV) is a commonly infected double-stranded DNA virus of the β-herpesviridae subfamily that typically establishes lifelong latency or persistent infection following primary infection. The regulation of HCMV latency and reactivation is governed by the chromatin structure at the viral major immediate early promoter (MIEP) within myeloid cells. Both cellular and viral factors play a role in regulating the reactivation of latent HCMV. Recently, it has been found that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) promotes HCMV reactivation in the clinic; however, the mechanism remains unclear. In this study, we found that SARS-CoV-2 ORF3a can activate HCMV MIEP by interacting with Yin Yang 1 (YY1), an inhibitor of MIEP. This interaction leads to YY1 ubiquitin-dependent degradation and subsequently promotes the reactivation of latent HCMV, as well as the replication and proliferation of the virus. These findings reveal the molecular mechanism underlying the interaction between SARS-CoV-2 and HCMV during co-infection, providing a new theoretical basis for future prevention and treatment strategies against the co-infection of these two viruses.